The Role of Storytelling in Teaching Critical Thinking Skills (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article researches how storytelling can be a beneficial pedagogical device for improving critical thinking skills among students. It applies the various ways storytelling teaches cognitive processes such as analysis, problem-solving, empathy, and reflection, all of are crucial for critical thinking. By delving into method educational practices, teachers can attract students in an effective learning experience.